2001
DOI: 10.1007/s002390010148
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Protein Structure, Selection, and Recombination on the Evolution of the Type-1 Fimbrial Major Subunit (fimA) from Escherichia coli

Abstract: Abstract. Fimbrial adhesins allow bacteria to interact with and attach to their environment. The bacteria possibly benefit from these interactions, but all external structures including adhesins also allow bacteria to be identified by other organisms. Thus adhesion molecules might be under multiple forms of selection including selection to constrain functional interactions or evolve novel epitopes to avoid recognition. We address these issues by studying genetic diversity in the Escherichia coli type-1 fimbria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
2
31
0
1
Order By: Relevance
“…Nevertheless, in some of the MLST genes analyzed here, the observed values of ω and n M are so high that it is hard to believe that LRTs are completely misleading in their conclusions, especially for M7-M8 comparisons (e.g., N. gonorrhoeae and S. agalactiae). Moreover, it has been shown that LRTs are conservative (Anisimova et al, 2001(Anisimova et al, ,2003Yang et al, 2000a), so genes inferred by the test to undergo positive selection are most likely true cases of adaptation rather than an artifact of the method, as proven in most of the published studies (e.g., Bishop et al, 2000;Peek et al, 2001;Yang et al, 2000b;Yang and Swanson, 2002). Besides, we have adopted an even more conservative approach since we are not considering the loci under significant positive selection for which positively selected sites were not identified.…”
Section: Species Comparisonsmentioning
confidence: 97%
“…Nevertheless, in some of the MLST genes analyzed here, the observed values of ω and n M are so high that it is hard to believe that LRTs are completely misleading in their conclusions, especially for M7-M8 comparisons (e.g., N. gonorrhoeae and S. agalactiae). Moreover, it has been shown that LRTs are conservative (Anisimova et al, 2001(Anisimova et al, ,2003Yang et al, 2000a), so genes inferred by the test to undergo positive selection are most likely true cases of adaptation rather than an artifact of the method, as proven in most of the published studies (e.g., Bishop et al, 2000;Peek et al, 2001;Yang et al, 2000b;Yang and Swanson, 2002). Besides, we have adopted an even more conservative approach since we are not considering the loci under significant positive selection for which positively selected sites were not identified.…”
Section: Species Comparisonsmentioning
confidence: 97%
“…The grouping was consistent throughout the six domains, although the last two variable domains are identical for groups two and three. Our comparison also included the original sequenced fimA by Marc and Dho-Moulin [13] (GenBank accession number Z37500) and a fimA from E. coli of mammalian origin, from Peek et al [15] (GenBank accession number AF206642). We also included a fimA sequence, amplified from an E. coli strain isolated from infected ostrich eggs.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that the E. coli strains of mammalian origin fell into one of the established groups and did not take an exclusive position. Even additional fimA sequences of mammalian origin from the study of Peek et al [15] were incorporated into the multiple alignment: all of them fell within the proposed groups and the established variable domains (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations